2003
DOI: 10.1002/rsa.10077
|View full text |Cite
|
Sign up to set email alerts
|

Random channel assignment in the plane

Abstract: ABSTRACT:In the model for random radio channel assignment considered here, points corresponding to transmitters are thrown down independently at random in the plane, and we must assign a radio channel to each point but avoid interference. In the most basic version of the model, we assume that there is a threshold d such that, in order to avoid interference, points within distance less than d must be assigned distinct channels. Thus we wish to color the nodes of a corresponding scaled unit disk graph. We consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 31 publications
3
55
0
Order By: Relevance
“…For sake of simplicity, let us suppose that this value of k is an integer. By (38) of Corollary 4, with high probability there is Θ(ln n) nodes inside the sphere of radius V 1/3 /2k. Consider now two adjacent sub-cubes as depicted in the figure below :…”
Section: Hop-diametermentioning
confidence: 91%
“…For sake of simplicity, let us suppose that this value of k is an integer. By (38) of Corollary 4, with high probability there is Θ(ln n) nodes inside the sphere of radius V 1/3 /2k. Consider now two adjacent sub-cubes as depicted in the figure below :…”
Section: Hop-diametermentioning
confidence: 91%
“…It can be observed that the transmitting power P x has no effect in the evaluation of Equation 25 for determining the occurrence of a collision, but it only affects the interrogation range. With the considered values of antenna gains and interrogation range in Table 1, we set the transmitting power to 30 dBm in order to make sure that the conventional RFID tags can be energized at 5 m.…”
Section: Methodsmentioning
confidence: 99%
“…This model [25] assumes that the readers are equipped with an omnidirectional antenna: their signal propagates in the same way along all the directions. Due to the path loss, there is a specific distance d beyond which the signal http://jes.eurasipjournals.com/content/2013/1/10 emitted by a reader is not powerful enough to feed the circuitry of a tag.…”
Section: Disk Graph Modelmentioning
confidence: 99%
“…e.g. [9], [13], [16], [17], [22], [23]. We particularly mention the work of the Hipercom Project, e.g.…”
Section: Introductionmentioning
confidence: 99%